Interventions to support the management of work-related stress (WRS) and wellbeing/mental health issues for commercial pilots - Cahill, Joan (My University, 2019)
Research indicates that sources of work-related stress (WRS) impact on the physical, social, and psychological health of pilots. Furthermore, specific features of the job can increase a pilot’s risk in relation to developing a mental health (MH) issue. It is impossible to remove all stress from the work life of pilots. A high stress situation may not necessarily be det-rimental to the person, once they have learned to cope with it in a healthy manner. Nonetheless, risk pertaining to WRS need to be effectively managed by a pilot’s employer. Therefore, it is important to identify solutions at an airline and pilot self-management level. This paper reports on the findings of human factors research undertaken with commercial pilots pertaining to work-related stress (WRS) and its impact on wellbeing, performance, and safety. The findings of a series of co-design workshops and a follow-up anonymous survey were analysed to identify potential solutions at (1) an airline and (2) pilot self-management level. Potential solutions are framed in relation to six impact scenarios. Furthermore, they are located within the existing regulatory framework, including the latest implementation rules (IR), acceptable means of compliance (ACM), and guidance material (GM) as outlined by the European Union Aviation Safety Agency (EASA 2019). Proposed interventions should promote wellbeing and positive mental health while also addressing suffering and mental ill health. Airline interventions might focus on enhancing existing Safety Management System (SMS) approaches to better manage risks pertaining to WRS, advancing new tools to enable wellbeing briefing, risk assessment, and reporting, and training pilots in relation to MH awareness, risk identifying behaviour, and coping strategies. Furthermore, new role/functions might be introduced to support the implementation and management of WRS/wellbeing/MH safety/risk processes at an airline level. Requirements for new digital tools to support pilot awareness of WRS/wellbeing/MH, self-management of WRS/wellbeing/MH and risk identification both inside and outside the cockpit are also proposed. Some of recommendations arising in this research require changes to the existing rule-making and/or modification to existing AMC and GM.
Keywords: Stress management; Wellbeing; Risk assessment; Self-management and performance; Work-related stress (WRS); Pilot mental health; Airline safety management systems; Safety; Inclusive Society; Smart & Sustainable Planet; Telecommunications; Health and Well being; Work Related Stress